Coronary arteriopathy in a patient with Noonan phenotype: Case report - Simran Jain; M. S. Ravindra; Yogesh Chintaman Sathe; Snehal M. Kulkarni; Ashish Banpurkar (Wolters Kluwer Medknow Publications, 2024)
Noonan syndrome (NS) is a pleomorphic genetic disorder. Up to 50-80% of individuals have associated congenital heart disease. The scope of cardiac disease in NS is quite variable depending on the gene mutation. The most common forms of cardiac defects include pulmonary stenosis, hypertrophic cardiomyopathy (HCM), atrial septal defect and left-sided lesions. Amongst the rare vascular abnormalities few case reports have been mentioned about coronary artery lesions apart from sinus of Valsalva aneurysm, aortic dissection, intracranial aneurysm. This is a case report a rare case of asymptomatic coronary artery aneurysm in a young male with NS. There is lack of unified protocol for the screening, diagnosis, treatment, and follow-up of coronary artery disease in patients with NS. We conclude, echocardiography is sufficient in most cases in children. But a CT scan is appropriate in adults or when other lesions are suspected.